Evaluation of our care model in patients with fragility hip fracture: Multidisciplinary team and Fracture Liaison Service. A three-year retrospective study - José S. Barreda-Puchades; Joan Andreu-Safont; Sara Linares-Aguayo; Rafael Ortiz-Ramón; Marta Ribelles-Férez; Alberto García-Roig; Pablo Cañete-Sanpastor (Journal of Orthopaedic Reports)
Introduction: To improve the patient's care with fragility hip fracture the association of orthogeriatric units with Fracture Liaison Service (FLS) units has been proposed as the one that more improves this function. The objective of our work is to assess the effectiveness of our care model. Material and methods: A retrospective study has been designed, in which the 255 patients who were admitted to the Traumatology service due to osteoporotic hip fracture in 2018 during a period of 3 years, have been assessed. For the statistical analysis, subsequent fractures and exitus have been selected as objective variables, and as explanatory variables: sex, age, treatment for osteoporosis, surgical delay and days of hospital stay. The association between the objective (categorical) and explanatory variables will be evaluated by a univariate analysis with a Pearson Chi-square test for categorical explanatory variables, or, with a Mann-Whitney-Wilcoxon test for continuous explanatory variables. Survival will be analyzed using the Kaplan-Meier method, comparing treatment groups with the log-Rank-test. Results: The mean age was 85,21 ± 6,87 years, with 183 women (76, 25 %) and 57 men (23,75 %). The most frequent fracture was pertrochanteric, with 111 (46.25 %) cases. A total of 117 patients were treated for osteoporosis. A significant relationship has been found between mortality and days of hospital stay (no exitus 8,89 days and with exitus 11,43 days). It is also observed that the percentage of patients with subsequent fractures is lower in treated patients (6.84 % versus untreated 11.32 %). The Kaplan-Meier survival analysis was slightly higher in treated patients, although it was not significant. Conclusion: It can be concluded that our care model could be an alternative to orthogeriatric units and that our FLS has a certain positive effect on survival and reduction of subsequent fractures, although not significantly.